Komparasi Pendapatan Bulanan Petani Karet Sistem Lelang Dengan Non Lelang Di Desa Anyar Buay Pemuka Bangsa Raja Ogan Komering Ulu Timur - Munsiarum; Gina Afriana (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2023)
This research was carried out in Anyar Village, Buay Pemuka Bangsa Raja District, OKU Timur District. The location determination was carried out purposively with the consideration that in Anyar Village there are some farmers who carry out rubber farming by selling the auction and non-auction systems. The research was carried out in January 2023. The aim of the research was to find out the process of determining the price of rubber latex by the auction system and to find out the comparison of the monthly income of rubber farmers with the auction and non-auction systems in Anyar Village, Buay Pemuka Bangsa Raja District, OKU Timur Regency The method used in this research is survey method. Respondents taken as samples were farmers who did rubber farming with a population of 91 rubber farmers consisting of 60 rubber farmers with an auction system and 31 non-auction rubber farmers. The results showed that the auction process was carried out behind closed doors, the auctioneer first determined the lowest price (the price of the complainant at the time of research was Rp. 9,201), which was attended by representatives from the three CVs participating in the auction market, namely those from Palembang, Lampung and Kayu Agung. The lowest price usually refers to the previous auction price in a neighboring village. The auction is carried out by means of bids from bidders which are written down on paper then rolled up and handed over directly to the auctioneer during the auction. After all bids have been submitted, the auctioneer will open the scrolls one by one and the winner is the bidder with the highest price (the highest price obtained is IDR 9,531). If someone is still able to exceed the previous highest price, the auction winner can still move on to the next highest bidder. The average income of rubber farmers with an auction system is IDR 1,650,534/month/ha while nonauction is IDR 1,437,099/month/ha. Mathematically there is a real (significant) difference between the auction system and non-auction crab farming income. This can be seen from the t-count value of 35.06 with the t-table value of 1.99.